Analysis of more than 20, 000 injuries in European professional football by using a citizen science-based approach: An opportunity for epidemiological research?. Issue 4 (April 2022) - Hoenig, Tim; Edouard, Pascal; Krause, Matthias; Malhan, Deeksha; Relógio, Angela; Junge, Astrid; Hollander, Karsten
Abstract: Objectives: It has been claimed that analyses of large datasets from publicly accessible, open-collaborated ("citizen science-based") online databases may provide additional insight into the epidemiology of injuries in professional football. However, this approach comes with major limitations, raising critical questions about the current trend of utilizing citizen science-based data. Therefore, we aimed to determine if citizen science-based health data from a popular online database on professional football players can be used for epidemiological research, i.e. in providing results comparable to other data sources used in previously published studies. Design: Retrospective database analysis. Methods: Transfermarkt.com (Transfermarkt; Hamburg; Germany) is a publicly accessible online database on various data of professional football players. All information provided in the section "injury history" of football players from the top five European leagues over a period of ten seasons (2009/10–2018/19) was analyzed. Frequency, characteristics, and incidence of injuries were reported according to seasons and countries, and results compared with three previously published databases (a scientific injury surveillance, a media-based study, and an insurance database). Results: Overall, 21, 598 injuries of 11, 507 players were analyzed from the Transfermarkt.com database. Incidence was 0.63 injuries per player-season (95% confidence interval 0.62 to 0.64) but significant differences between subgroups (countries, years) were found. In comparison to other databases, citizen science-based data was associated with lower injury incidences and higher proportions of severe injuries. Conclusions: With few exceptions (e.g., severe injuries), the use of citizen science-based health data on professional football players cannot be recommended at present for epidemiological research.